Counselling Diverse Groups: Addressing Counsellor Bias toward the BDSM and D/S Subculture - Hillier, Kaitlyn M. (Canadian Journal of Counselling and Psychotherapy, 2018)
This article focuses on the professional bias or negative perceptions of some mental health professionals toward the bondage, domination, sadism/submission, and masochism (BDSM) community and dominant/submissive (D/S) relationships. This article suggests and recommends measures for culturally sensitive practice and the inclusion of psychodynamic family therapy approaches that would be positively inclusive of this unique sexual lifestyle as an effective approach for clients who engage in BDSM. Measures described could increase professional competency in established and training mental health professionals who may work with clients who practice BDSM.